Pemanfaatan Limbah Konsumsi Ikan dari Warung Lesehan dan Warung Sea Food untuk Pengganti Sebagian Pakan Ayam Broiler - Pepy Martha Agyani; Tuntas Bagyono; Adib Suyanto (Poltekkes Kemenkes Yogyakarta, 2016)
Waste is material or substance, both organic and inorganic in nature, which is resulted from any human activity. Another alternative for organic waste treatment, other than composting, is to convert it as an ingredient for animal feed. The aim of this study was to determine the effect of fish waste flour used as feed toward the increase of the body weight of broiler chickens. The feed were made by the researchers and consist of 28 % fish consumption waste flour, 24 % tofu dregs, and 48 % rice bran. By that proportion, protein content in the feed was measured as much as 24 %. The design of this study was pre-test post-test control group. BR1 that available in markets was as the control feed, and the number of chicken sample in each study group was 20.The dependent variable measured was the percentage of body weight increase gained duringthree weeks feeding. The results show that in average, in the control group, the chickens obtained weight as much as 95,73 %; meanwhile in the treatment group, the chickens were 95,99 %heavier. The analysis by using Wilcoxon test at 95 % level of significance comes to conclusionthat those weight gains are significantly different (p-value: 0,002). It is suggested for the community, especially broiler breeders, to choose feed ingredients that contain high protein but not expensive, easy to get and easy to manage, as has been shown by this study.